CRIMINAL RESPONSIBILITY OF SHAREHOLDERS IN THE SEMI-PUBLIC COMPANY ON THE MONEY LAUNDERING CRIME IN INDONESIA - Sulistyanta, Winarno Budyatmojo, Jemmy Tanjung Utama (Chelonian Research Foundation, 2023)
Money laundering is often committed by powerful people, involving many parties, including companies and shareholders, a crime intended to accumulate and maintain wealth generated illegally. This study aimed to examine the criminal responsibility of shareholders and how the criminal law policy prevent money laundering. The data was collected through library techniques and analyzed using descriptive qualitative methods. The results showed that though the actual crime is committed by the directors and the commissioners of the semi-public company, the shareholders could also be held criminally responsible for money laundering. Since the shareholders are not regulated in the criminal law as a responsible party, it is challenging to include them in a money laundering case.